Концепція транспортного кластера сітілогістики - Губенко, В. К.; Ніколаєнко, І. В.; Лямзін, А. О. (Видавництво Львівської політехніки, 2012)
Розглянуто теоретичні аспекти створення транспортного кластера сітілогістики на принципах теорії систем і системного аналізу. Розроблено концептуальні основи формування структури транспортного кластера сітілогістики. Запропоновано формалізований запис умови існування системи транспортного кластера з урахуванням методів придатності, оптимальності й адаптивності. Сформульовані чинники, які впливають на ефективність організації транспортного кластера сітілогістики. Розглянуто потенціал та ефективність транспортного кластера. The author considers theoretical aspects of a city logistics transport cluster creation basing herself on the principles of the systems theory and systems analysis. Structural classification of a city logistics transport cluster has been executed and its hierarchical levels have been identified. A formalized formula of the condition of the transport cluster system existence is proposed, taking into account the methods of applicability, optimization and adaptability. Basic structural, organisational and harmonization principles of a city logistics transport cluster are analysed. The potential and efficiency of a transport cluster are considered. Factors which impact the efficiency of organization of a city logistics transport cluster are formulated. Comparative description of a cluster іs branch approach in a business environment of an urban transport system is given in the article. The creative decisions in the supply chains of city logistics are analysed on the basis of structural-functional decoupling of a transport cluster.
Conception of a city logistics transport cluster
Keywords: концепція; транспортний кластер; сітілогістика; міська транспортна система; conception; transport cluster; city logistics; urban transport system